Health complaints and heat stress prevention strategies during taper as predictors of peaked athletic performance at the 2015 World Athletics Championship in hot conditions. Issue 4 (April 2020) - Timpka, Toomas; Périard, Julien D.; Spreco, Armin; Dahlström, Örjan; Jacobsson, Jenny; Bargoria, Victor; Andersson, Christer; Alonso, Juan-Manuel; Racinais, Sébastien
Abstract: Objectives: To investigate whether self-reported health complaints and choice of heat stress prevention strategies during the taper predicted peaking at an athletics championship in hot conditions. Design: Cohort study. Methods: Data on health and heat stress prevention were collected before the 2015 World Athletics Championship in Beijing, China. Peaking was defined using the athlete's pre-competition ranking and final competition rank. Baseline and endpoint data were fitted into multiple logic regression models. Results: Two hundred forty-five (29%) of 841 eligible athletes participated. Both sprint/power (Odds ratio (OR) 0.33 (95% Confidence interval (CI) 0.11 to 0.94), P  = 0.038) and endurance/combined events (OR 0.38 (95% CI 0.14 to 1.00), P  = 0.049) athletes having sustained concern-causing health complaints during the taper were less likely to peak. Endurance/combined events athletes who chose pre-cooling to mitigate heat stress were less likely to peak (OR 0.35 (95% CI 0.15 to 0.80), P  = 0.013), while sprint/power athletes reporting a sudden-onset injury complaint during the taper displayed increased peaking (OR 4.47 (95% CI 1.28 to 15.59), P  = 0.019). Conclusions: Health complaints that caused the athlete concern during the taper were predictive of failure to peak at a major athletics competition. Sprint/power athletes who experienced an acute injury symptom during the taper appeared to benefit from rest. Pre-cooling strategies seem to require further validation during real-world endurance/combined events. It appears that athletics athletes' self-reported health should be monitored during the taper, concerns addressed, and heat stress prevention strategies individually tested before championships in hot conditions.